Acrolein evokes inflammation and autophagy-dependent apoptosis through oxidative stress in vascular endothelial cells and its protection by 6-C-(E-2-fluorostyryl)naringenin. (November 2022) - Zhou, Yue; Xu, Hui; Cheng, Ka-Wing; Chen, Feng; Zhou, Qian; Wang, Mingfu
Graphical abstract: Highlights: Acrolein induced mitochondrial dysfunction, apoptosis, and inflammation in HUVECs. Acrolein induced apoptosis was partially dependent on the activation of autophagy. The addition of styryl group contributed to the protective potential of 6- C -( E -fluorostyryl)naringenin. The protective effects of 6- C -( E -fluorostyryl)naringenin is via Nrf2 activation. Abstract: Acrolein is a common dietary and environmental toxicant. Evidence suggests that acrolein can increase the risk of cardiovascular diseases in which endothelial cells are the sensitive targets. In human umbilical vein endothelial cells (HUVECs), acrolein treatment induced mitochondrial dysfunction, which subsequently triggered apoptosis and inflammation. Acrolein also upregulated autophagy, which possibly resulted from negative regulation of the protein kinase B (Akt)/mammalian target of rapamycin (mTOR) pathway via reactive oxygen species (ROS). Inhibition of autophagy by 3-methyladenine reduced acrolein-evoked apoptosis, implying a pro-death role of autophagy. In addition, the protective potential of 6- C -( E -2-fluorostyryl)naringenin (6-CEFN) against acrolein was examined. 6-CEFN exhibited higher efficacy than its parental compound naringenin in preventing acrolein-caused damages, where nuclear factor erythroid 2-related factor (Nrf2)-mediated up-regulation of phase II enzymes was involved. Altogether, our findings offer new mechanistic insights into acrolein-induced endothelial injury and demonstrate the therapeutic potential of 6-CEFN for acrolein-related cardiovascular toxicities.